Effectiveness of Cognitive Restructuring Counselling Technique in Managing Anxiety Among Couples with Infertility Challenges in Gombe State, Nigeria - Ishaka, , Yahaya (Kashere Journal of Education, 2021)
This study investigated the effectiveness of cognitive restructuring counselling technique in managing anxiety among couples with infertility challenges in Gombe State, Nigeria. The population of this study was seventy-six (76) couples of reproductive age with infertility challenges that were registered and receiving infertility treatment at the two Government owned hospitals selected for this study. These are: Federal teaching hospital, Gombe and Specialist Hospital Gombe. Forty-two (42) patients accessing infertility treatment from Federal teaching hospital and thirty-four (34) patients accessing infertility treatment from specialist hospital Gombe (i.e. 42+34 = 76). Thirty-eight (38) couples were selected to participate in the study. The researcher employed quasi-experimental pre-test/post-test and control group design, in which selected couples were assigned to two experimental groups. The experimental group were treated with cognitive restructuring counselling tecnique while the control group didn’t receive any treatment. The treatments were carried out within eight weeks of counselling sessions. Group counselling method was employed in the study. Each of the subjects was administered with pre test/post-test research instrument using Beck Anxiety Inventory (BAI) Two research objectives and two research hypotheses were formulated. The data collected were analyzed using dependent sample t-test to test hypothesis 1 and independent t-test was used to test hypothesis 2 at 0.05 level of significance. Results from data analysis revealed that cognitive restructuring counselling technique was effective in managing anxiety among couples with infertility challenges. It was also recommended that cognitive restructuring should be used in managing anxiety level of couples faced with infertility challenges in various health centres.